Research of Physiological Factors Affecting Pilot Performance in Flight Simulation Training Device - Novak, Andrej; Mrazova, Maria (Communications - Scientific letters of the University of Zilina, 2015)
Physiological factors can easily affect a pilot performance and jeopardise the safety of the flight. Therefore, the research is based on the observation of student pilots’ decision making and flying abilities during different flight conditions predetermined for the flight in simulation training device. The use of flight simulation training device is helpful as it is possible to vary flight parameters and consequently observe the pilot’s reactions to different situations. The combination of pilot error statistics and subjective questionnaire enable to determine the influence of external conditions on the pilot’s psychological state and subsequent performance during critical flight tasks.